Is there a bubble in the Chinese housing market? - Christian Dreger; Yanqun Zhang (European Regional Science Association (ERSA), 2011)
For many analysts, the Chinese economy is spurred by a bubble in the housing market, probably driven by the fiscal stimulus package and massive credit expansion, with possible adverse effects to the real economy. For example, the stock of loans increased by more than 50 percent since the end of 2008. The government urged banks to increase lending to mitigate the economic slowdown. Home mortgage loans have played a significant role in the development, as they account for one third of the total lending activities. Banks have provided easy credit for housing development, probably without sufficient evaluation of risks. State-owned enterprises may have stimulated the development, as they have access to low cost capital and may believe they are too big to fail. In this paper, the house price development is investigated both at the national and regional level. First, it is investigated whether a bubble exists. Analysis is based on a long run equilibrium between real house prices and demographic and macroeconomic conditions. Using a regional dataset for 35 major Chinese cities, the size of the bubble is estimated relative to the fundamental level implied by the panel cointegrating relationship. Second, the impact of real house prices on CPI inflation and GDP growth is investigated at the national level using an in sample and out of sample framework. The results indicate the presence of a house price bubble. Real house prices are 25 percent above their equilibrium value. The bubble is especially pronounced in the cities of the southeast coastal areas and the special economic zones. While the impact of real house prices on CPI inflation seems to be rather strong, GDP growth may not be heavily affected. Real house prices do not cause GDP growth, and point forecasts of GDP growth are not improved if the house price evolution is taken into account. These findings might reflect a limited exposure of private households expenditures to housing wealth. Therefore, a decline of the bubble could have only modest effects on the course of the real economy.
Keywords: 330